2006
DOI: 10.1097/00005110-200601000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analyses of Nurse Staffing and Patient Outcomes

Abstract: The overall conclusion is that it will likely be necessary to vary staffing hours and staffing mix depending on which positive patient outcome or outcomes you wish to achieve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 11 publications
1
69
2
Order By: Relevance
“…Studies found no association with mortality (Unruh et al, 2007), failure to rescue (Park et al, 2012), length of stay (Unruh et al, 2007), venous thromboembolism (Ibe et al, 2008), or missed care . However, higher assistant staffing was associated with higher rates of falls (Hart andDavis, 2011, Lake et al, 2010), pressure ulcers (Seago et al, 2006), readmission rates (Weiss et al, 2011), medication errors (Seago et al, 2006), use of physical restraints M a n u s c r i p t…”
Section: O U T C O M E S a S S O C I A T E D W I T H N U R S I N G A mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies found no association with mortality (Unruh et al, 2007), failure to rescue (Park et al, 2012), length of stay (Unruh et al, 2007), venous thromboembolism (Ibe et al, 2008), or missed care . However, higher assistant staffing was associated with higher rates of falls (Hart andDavis, 2011, Lake et al, 2010), pressure ulcers (Seago et al, 2006), readmission rates (Weiss et al, 2011), medication errors (Seago et al, 2006), use of physical restraints M a n u s c r i p t…”
Section: O U T C O M E S a S S O C I A T E D W I T H N U R S I N G A mentioning
confidence: 99%
“…Page 11 (Hart and Davis, 2011) and lower levels of patient satisfaction (Seago et al, 2006), although one weak study found that higher HCA staffing levels were associated with lower rates of pressure ulcers (Ibe et al, 2008). …”
Section: March 2016mentioning
confidence: 99%
“…Studies of nurseto-patient ratios find that adequate staffing is associated with fewer adverse events (2,102). In contrast, less adequate staffing levels (indicated by workload, overtime, or increased nonregistered nurse hours of care) resulted in unexpected deaths (28) and medication errors (132).…”
Section: Internal Motivatorsmentioning
confidence: 99%
“…Antitumor drug therapy may require nursing services that are not properly evaluated by the NND. A number of studies have suggested that adequate staffing is associated with improved patient outcomes [13][14][15]. Moreover, high patient-to-nurse ratios more likely lead to low burnout and dissatisfaction [15,16].…”
Section: X>$10732 18mentioning
confidence: 99%
“…A number of studies have suggested that adequate staffing is associated with improved patient outcomes [13][14][15]. Moreover, high patient-to-nurse ratios more likely lead to low burnout and dissatisfaction [15,16]. Future studies are needed to clarify the number of nurses required for antitumor drug therapy under the classification of NND.…”
Section: X>$10732 18mentioning
confidence: 99%